2020
DOI: 10.1088/1755-1315/615/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Electricity market dynamics: The influence of fuel prices and the spillover effect

Abstract: Fossil energy power generation still plays a key role in the power generation industry, especially for countries where thermal power generation still dominates. With such potential considerable impact, this article aims to analyze the drivers of peak and valley electricity prices from the perspective of thermal power fuel. Specifically, the study uses data from the highly market-oriented US PJM power market to conduct an empirical analysis and focused on the links with coal, crude oil, and natural gas. Applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, the spillover effect of the electricity price reduction could benefit all industries and all entities. Previous studies have already confirmed this point [46,47]. Electricity prices are always closely correlated to many commodities and production sections, which could eventually induce an influence on all industries.…”
Section: Price-cutting Policy Optimizationmentioning
confidence: 70%
“…Moreover, the spillover effect of the electricity price reduction could benefit all industries and all entities. Previous studies have already confirmed this point [46,47]. Electricity prices are always closely correlated to many commodities and production sections, which could eventually induce an influence on all industries.…”
Section: Price-cutting Policy Optimizationmentioning
confidence: 70%
“…Nakajima (2013) examined the electricity market in Japan and found that oil and gas prices do not cause Granger causality to the price of electricity. Ding et al (2020) analyzed peak electricity prices, finding a short-term bidirectional spillover effect between thermal energy fuels and the electricity market, with natural gas playing a critical role in transmitting information to electricity prices. Muñoz and Dickey (2009) highlighted the volatility between oil and electricity prices in Spain.…”
Section: The Price Of Oil Gas and Energymentioning
confidence: 99%